Dynamics of homocysteine precursors and methylation index in high-class biathletes at the stages of the preparatory period of the annual cycle - Dikunets, M. A.; Dudko, G. A.; Viryus, E. D.; Fedotova, E. V. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify the dynamics of S-adenosylmethionine, S-adenosylhomocysteine and methylation index in high-class biathletes at the stages of the preparatory period of the annual cycle.